Three-dimensional cloud-resolving modeling of the flash-flood heavy rainfall event over Kosovo - Osmanaj, Lavdim; Spiridonov, Irena; Jakimovski, B.; Spiridonov, Vlado (Springer Science and Business Media LLC, 2024)
This study examines the severe flash flood event that hit Kosovo on June 24, 2023, resulting in an extraordinary 54 mm of rainfall within a single hour. Utilizing a state-of-the-art three-dimensional nonhydrostatic cloud resolving model, the research clarifies the atmospheric mechanisms driving such extreme precipitation events. Key findings highlight the development of high altitude cumulonimbus clouds, the crucial role of strong updrafts in facilitating intense microphysical vertical transfer, and the subsequent formation of wet downbursts. Model validation against radar data demonstrates accuracy in replicating observed precipitation patterns, bolstering confidence in its predictive capabilities. These insights enhance our understanding of extreme weather events and suggest potential improvements in forecasting and risk mitigation strategies.